Generic redescription, two new species, and a key to the species of the cicada genus Ariasa Distant, 1905 with the description of a new genus (Hemiptera: Cicadidae: Cicadinae: Fidicinini) - Sanborn, Allen F. (Zootaxa, 2016)
The cicada genus Ariasa Distant, 1905 is redescribed.  Ariasa albimaculosa n. sp. is described from Colombia and A. bartletti n. sp. is described from Peru.  The current 14 species of Ariasa are listed along with their synonymies, known distribution of each species, and a key to the species is provided.  The first records of Ariasa bilaqueata (Uhler, 1903) for Peru and French Guiana are provided. Cracenpsaltria brasiliorum (Kirkaldy, 1909) rev. stat., n. comb. is determined to be the correct name for the taxon Cicada marginata Olivier, 1790 and the new genus Cracenpsaltria n. gen. is erected for the taxon.  The distribution of C. brasiliorum rev. stat., n. comb. is expanded to include Bolivia and Peru.